Marketing Strategies for "Pak De's Tempeh Chips": Enhancing Business Income and Performance - Siti Anggun Ramadhani Br Sinaga; Desi Indah Safitri; Muhammad Rasya (Young Journal of Social Sciences and Humanities, 2025)
Marketing strategy plays a crucial role in driving revenue growth and strengthening the market position of small businesses, particularly in competitive sectors where differentiation and consumer engagement are key. This study examines the marketing strategies employed by "Pak De Tempe Chips", a local culinary product made from tempeh, recognized as a distinctive traditional snack. Using a qualitative research approach, data were collected through in-depth interviews with the business owner, analysis of relevant documentation, and direct observation of the company's marketing activities. The research focuses on several strategic aspects, including the implementation of digital marketing techniques through social media platforms, offline promotional efforts, development of attractive and functional product packaging, and competitive pricing strategies. The findings indicate that this combination of marketing practices effectively enhances the visibility of the product, attracts new customers, and strengthens loyalty among existing consumers. In addition, innovations in flavor variants and responsive, personalized customer service have a significant impact on increasing revenue and differentiating the product in the market. The study provides practical insights and serves as a valuable reference for small business owners seeking to optimize marketing strategies, expand market reach, and improve profitability, particularly in the traditional and local food industry segment, where creativity and customer trust are essential for sustained growth.